The effect of confinement on the electronic energy and polarizability of a hydrogen molecular ion - Silva, Josimar Fernando da [UNESP]; Silva, Fabricio Ramos [UNESP]; Drigo Filho, Elso [UNESP] (Wiley-Blackwell, 2016)
The electronic energy and the polarizability of a confined hydrogen molecular ion in the ground state and the first excited state, for cavities of different volumes, are calculated using the variational method. In the treatment adopted an alternative molecular wave function is introduced with only one variational parameter and based on wave functions used for confined atoms. (c) 2016 Wiley Periodicals, Inc.
Keywords: variational method; confined molecule; hydrogen molecular ion; electronic energy; polarizability